2020
DOI: 10.32479/ijeep.8140
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Energy Consumption Based on Fossil Fuel and Hydroelectricity Generation Towards Pollution in Malaysia, Indonesia and Thailand

Abstract: This study investigated the effects of energy consumption (ENY) based on fossil fuels and alternative energy with hydroelectricity as its proxy upon pollution, aside from ascertaining if the correlation between income and pollution determined the presence of Environmental Kuznets curve (EKC). In addition, the functions of foreign direct investment (FDI) inflows and trade openness (TO) were probed into so as to generate more precise outcomes of EKC hypothesis. Hence, in order to fulfil the objectives outlined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
2
22
1
1
Order By: Relevance
“…This implies that an upsurge in hydroelectricity aids in mitigating environmental degradation in China. This outcome is consistent with the studies of Solarin et al [ 30 ], Kivyiro and Arminen [ 42 ], Gyamfi et al [ 11 ], and Ridzuan et al [ 41 ] who established a negative linkage between hydroelectricity and environmental deterioration.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This implies that an upsurge in hydroelectricity aids in mitigating environmental degradation in China. This outcome is consistent with the studies of Solarin et al [ 30 ], Kivyiro and Arminen [ 42 ], Gyamfi et al [ 11 ], and Ridzuan et al [ 41 ] who established a negative linkage between hydroelectricity and environmental deterioration.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, following the studies of [17,29], we incorporated the URB into the model. Lastly, we introduced HYDRO into the model following the studies of [11,30,41,42]. The cointegration test may be performed using the F-test on the lagged levels of the variables [43].…”
Section: Empirical Methodologymentioning
confidence: 99%
“…In this section, relevant empirical studies support the connection between carbon dioxide emissions, economic growth, urban population, and renewable energy. Recently, scholars like (e.g., Grossman and Krueger [7,8]; Douglas and Selden [9]; Balogh and Jambor [10]; Apergis [11]; Saudi et al [12]; Ridzuan et al [13] used environmental Kuznets curve (EKC) assumptions to evaluate the impact of income per capita, squared income per capita, energy, and international trade on CO 2 emissions. The EKC hypothesis (See Figure 1) considers that there is a direct impact of income per capita on carbon dioxide emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same line, the empirical Moreover, the econometric results also showed that the variable of energy consumption presents a positive impact on carbon emissions, and renewable energy is negatively correlated with carbon emissions, as the previous studies. In the same line, the empirical research of Ridzuan et al [13] evaluated the effects of energy consumption, income per capita, squared income per capita, trade openness, and foreign direct investment on carbon emissions by Malaysia, Indonesia, and Thailand. The econometric results with the autoregressive distributed lag-ARDL model, in the long-run, demonstrated that income per capita presents a positive effect on carbon emission by Malaysia and Thailand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The huge use of fossil fuels can cause various forms of visible and serious damage to the environment (Ridzuan et al, 2018;Nada et al, 2014). According to Ridzuan et al (2019), Ridzuan et al (2020a); Ridzuan et al (2020b), Ridzuan et al (2021b), Md Razak et al (2017 and Hezareh et al (2017), energy use rises CO 2 emissions. However, Belke et al (2011) and Marinas et al (2018) argued that energy use should not be reduced as it can disrupt economic growth.…”
Section: Introductionmentioning
confidence: 99%